Antiulcer and antiproliferative properties of spent brewer's yeast peptide extracts for incorporation into foods - Amorim, Maria M; Pereira, Joana O; Monteiro, Karin M; Ruiz, Ana L; Carvalho, João E; Pinheiro, Hélder; Pintado, Manuela (Food & function, 2016)
The main objective was to study the antiulcer and antiproliferative potential of yeast peptide extract for further incorporation into functional foods. Peptide concentrates were obtained by hydrolysis of spent brewer's yeast proteins followed by a filtration process. In order to prove the possible protection of gastric mucosa, an animal model with ulcerative lesions caused by oral administration of absolute ethanol was used. The peptide fraction <3 kDa was able to reduce gastric injuries to significant levels ( p < 0.001) and the effective dose (DE 50 ) was 816 mg per kg bw. The cytoprotective effect appears to depend on a prostaglandin-mediated mechanism and also on a nonspecific mechanism. The antiproliferative activity of the extract in nine different human tumoral cell lines was tested. The results exhibited a promising antiproliferative activity against the cell line K-562 (leukemia). The results suggest that a new peptide extract can be used to develop new value-added functional food products, although further studies are required. The main objective was to study the antiulcer and antiproliferative potential of yeast peptide extract for further incorporation into functional foods.